Ceramic particle reinforced wear-resistant cast steel and preparation method thereof
Through the in-situ synthesis of high-hardness titanium carbide ceramic phase and smelting technology, the problem of ceramic particles being easy to peel off under wear load is solved, and the high hardness and excellent wear resistance of ceramic particles strengthened wear-resistant cast steel is achieved, which significantly improves wear and tear performance.
Patent Information
- Application Number
- CN202411052260.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-13
AI Technical Summary
The existing ceramic reinforced steels are prone to peel off under the action of wear loads, resulting in poor bonding effect and affecting wear resistance.
In-situ synthesis method is used to generate high-hardness titanium carbide (TiC) ceramic phase in wear-resistant cast steel, and through the combination of smelting high-titanium steel water and medium-carbon silicon-manganese-chromium alloy steel water, the TiC ceramic particle size is small and distributed. Even.
The high hardness and excellent wear resistance of ceramic particle-strengthened wear-resistant cast steel are achieved, with a macroscopic hardness greater than 65HRC, and the wear resistance is 280%, 220% and 130% higher than that of traditional materials, and good strength and toughness are maintained.
Smart Images

Figure BDA0004975251930000141
Abstract
Description
Technical Field
[0001] The invention discloses a wear-resistant cast steel and a preparation method thereof, in particular to a ceramic particle reinforced wear-resistant cast steel and a preparation method thereof, belonging to the technical field of wear-resistant materials. Background Art
[0002] As a common structural material, steel castings are widely used in various mechanical equipment or parts. Their quality directly affects the service life, normal working stability and safety of the equipment. Especially in special machinery or engineering, steel castings often serve as key vulnerable parts of the equipment. Whether they have excellent wear characteristics largely determines the service life and use effect of the equipment. Therefore, it is particularly important to develop wear-resistant steel castings with excellent comprehensive performance based on the material and preparation process of steel castings.
[0003] In order to improve the performance of wear-resistant cast steel, Chinese invention patent CN115652185A discloses a method for preparing high-strength low-alloy wear-resistant cast steel, which is obtained by modifying the low-alloy cast steel ZG30MnSi material with a Re-B-Ti microalloy composite modifier, and the final chemical composition and mass percentage are: 0.25-0.35C, 1.1-1.4Mn, 0.6-0.8Si, 0.002-0.005B, 0.02-0.05Ti, the total amount of Re and La ≤0.1, S / P ≤0.03, and the rest are Fe and residual elements. The above cast steel is subjected to normalizing + quenching + low-temperature tempering heat treatment, and the metallographic structure after heat treatment is: tempered martensite. The tensile strength of the wear-resistant cast steel is ≥1500MPa, the hardness HRC ≥50, and the V-notch impact energy K V2≥18J. Chinese invention patent CN114318160A also discloses a rare earth reinforced troostite mining groove wear-resistant cast steel and its manufacturing method. The chemical composition of the wear-resistant groove cast steel is C: 0.25-0.45; Mn: 0.90-1.80; Si: 0.45-1.35; Re: 0.01-0.03; S≤0.030; P≤0.030; the balance is Fe and inevitable impurity elements. The manufacturing process of the groove cast steel includes: converter or electric furnace smelting, refining outside the furnace, groove mold casting, unpacking, and heat treatment. According to the above composition and process, the strength of the mining groove wear-resistant cast steel is more than 1000MPa, and the wear resistance can reach more than 1.5 times that of ZG30MnSiMo, and the machining performance and welding performance are excellent, which can meet the use requirements of the middle groove of the mining scraper conveyor. Chinese invention patent CN113930581A also discloses a method for refining and passivating cast carbides of high carbon wear-resistant cast steel by melt modification, and controlling the morphology, size and distribution of carbides in combination with subsequent heat treatment. The carbide control method includes the following steps: induction furnace or electric furnace smelting → LF refining → feeding wire and adding appropriate amount of melt modifier → pouring casting → casting annealing → casting quenching or normalizing → casting tempering; wherein: LF refining is selectively performed according to the requirements of the cast steel refining process, and if LF refining is not required, directly proceed to the next step; after selective LF refining, an appropriate amount of melt modifier is added by feeding wire; the casting is heat treated with corresponding process parameters according to the composition of the cast steel. The invention can effectively control the carbides in the cast state of high carbon wear-resistant steel, and improve the composition segregation of the casting while refining and passivating the cast carbides. After subsequent heat treatment, nano-spherical carbides are dispersed in the steel matrix. Chinese invention patent CN113046648A also discloses a wear-resistant cast steel, the composition of which is: C: 0.85%~1.0wt%, Si: 1.8%~2.0wt%, Mn: 2.0%~2.1wt%, Cr: 0.8~1.2wt%, Mo: 0.2%~0.3wt%, Nb: 0.01~0.03wt%, P: ≤0.04wt%, S: ≤0.04wt%, Al: 0.04~0.09wt%, and the balance is Fe. The wear-resistant cast steel provided by the invention is used for the production of cylinder liner tooling base, which overcomes the shortcomings of low strength, poor wear resistance, and low service life of ordinary tooling bases. The room temperature tensile strength of the wear-resistant cast steel provided by the invention is as high as about 1000MPa, which is much higher than the strength level of about 600MPa of the existing 45 steel cylinder liner base, and has high wear resistance and service life, which can greatly reduce the replacement life of the tooling base. Chinese invention patent CN112662957A also discloses a bainite wear-resistant cast steel with strong wear hardening ability and a preparation method and application thereof.The chemical composition and mass content of the strong wear hardening bainitic wear-resistant cast steel provided by the present invention are as follows: C: 0.45%-0.60%, Si: 2.0-3.0%, Mn: 1.5-2.5%, Cr: 0.8-1.2%, Mo: 0.4-0.8%, Cu: 0.4-0.7%, RE: 0.03-0.06%, P≤0.040%, S≤0.040%, and the balance is iron and inevitable impurities. The strong wear hardening bainitic wear-resistant cast steel of the present invention has extremely strong wear resistance under medium and high stresses. The strong wear hardening bainitic wear-resistant cast steel of the present invention has good application prospects in wear-resistant parts of large impact abrasive wear conditions such as large crusher hammers. Chinese invention patent CN110157974A also discloses a high-hardness high-boron wear-resistant cast steel and a preparation method thereof. The chemical composition of the high-hardness, high-boron wear-resistant cast steel is: B is 1.5-3.0wt%; C is 0.2-0.8wt%; Al is 0.5-0.8wt%; Si is 0.7-1.0wt%; Mn is 4.0-7.0wt%; Ti is 0.3-0.5wt%; Ce is 0.4-0.6wt%; Mg is 0.4-0.6wt%; S < 0.03wt%; P < 0.04wt%; the balance is Fe and unavoidable impurities. First, scrap steel, pig iron, ferroboron, ferrosilicon, ferromanganese, ferrotitanium, rare earth magnesium silicon alloy, rare earth ferrosilicon alloy and carburizer are mixed according to the chemical composition, and then ferrotitanium, rare earth magnesium silicon alloy and rare earth ferrosilicon alloy are pre-placed at the bottom of the ladle; then, the molten steel smelted by other ingredients is poured into the ladle, cast and formed by an iron mold, cooled, and tempered to obtain high-hardness, high-boron wear-resistant cast steel. The invention has a simple process and low preparation cost, and the prepared high-hardness, high-boron wear-resistant cast steel has not only high hardness, but also good toughness and wear resistance. Chinese invention patent CN109778068A also discloses a wear-resistant cast steel reinforced with niobium and vanadium and its preparation method, comprising C0.38-0.42%, Si0.60-1.10%, Mn0.80-1.20%, Cr1.60-2.0%, Mo0.35-0.65%, V0.06-0.09%, Nb0.02-0.06%, Ni0.30-0.6%, La+Ce≤0.05%, P≤0.025%, S≤0.015% and the balance Fe and inevitable impurities; during preparation, the cast product with the same composition as the wear-resistant cast steel is annealed, quenched and tempered in sequence. However, the various wear-resistant cast steels successfully developed at present still have the disadvantages of low hardness, small amount of wear-resistant hard phase and poor wear resistance.
[0004] In order to further improve the wear resistance of cast steel, adding ceramic reinforcement phase to cast steel is beneficial to improve the wear resistance of steel. Chinese invention patent CN113683402A discloses a ceramic composite wear-resistant steel ball, which is characterized in that the ceramic preform is neatly spliced and arranged along the inner surface of the mold, and then the metal melt is cast into the mold, and the ceramic composite wear-resistant steel ball is obtained by heat treatment; wherein, the raw materials of the ceramic preform include by weight: 90 parts of zirconium oxide toughened alumina ceramic particles, 1-3 parts of active powder, 3-4 parts of kaolin, and 3-6 parts of adhesive; the active powder is a combination of nano titanium oxide, nano niobium oxide and nano yttrium oxide; the weight ratio of nano titanium oxide, nano niobium oxide and nano yttrium oxide is 1:0.4-0.6:0.4-0.6; the adhesive is a combination of water glass and carboxymethyl cellulose; the weight ratio of water glass and carboxymethyl cellulose is 1-2:1; in the preparation process of the ceramic preform, The zirconia toughened alumina ceramic particles, active powder, kaolin, and adhesive aqueous solution are mixed and defoamed, then injected into a mold for shaping, heated to 1200-1300°C at a rate of 3-4°C / min, and sintered for 3-4 hours to obtain a ceramic preform; the raw materials of the metal melt include, by weight percentage, C: 1.8-2.0%, Cr: 10.0-11.0%, Mn: 0.5-0.7%, Si: 0.4-0.7%, P≤0.05%, S≤0.05%, and the remainder is Fe and unavoidable impurities; the casting temperature of the metal melt is 1520-1540°C; the heat treatment procedure is: at 890-910°C, keep warm for 2.5-3.5 hours, quench with water, then heat to 220-240°C for tempering for 2-2.5 hours, and cool to room temperature. Chinese invention patent CN110484760A also discloses a new type of ceramic wear-resistant composite material, which includes, by weight, 70-80% steel, 2-3% kaolin, 3-5% bauxite, 3-8% quartz sand, 1-3% mica, 1-2% bentonite, 1-2% kyanite, 1-2% barite, 1-2% calcite, 1-2% graphite, 1-2% fluorite, 1-2% feldspar, 1-2% mullite, 0.5-1.5% SiC, 1-2% zeolite, 1-3% wollastonite, 1-2% spinel, 1-2% crystal stone and 1-2% aluminum magnesium ore. The new type of ceramic wear-resistant composite material has high strength, hardness and wear resistance, and can replace conventional precious metal wear-resistant steel, so as to be applied to industries with severe wear and tear, and to manufacture parts that withstand severe wear and strong impact, such as vehicle tracks, excavator buckets, crusher jaws and rail forks.Chinese invention patent CN109455935A also discloses a composite material of alumina ceramic and wear-resistant steel, including a wear-resistant steel substrate, a ceramic layer and an enamel layer, wherein the enamel layer is located between the wear-resistant steel substrate and the ceramic layer, and also provides a preparation method of the composite material: decarburizing the wear-resistant steel substrate to obtain a wear-resistant steel substrate, preparing enamel powder and ceramic particles, and then sequentially placing the above materials into a mold, bidirectionally pressurizing, and then sintering at normal pressure to obtain a composite material of alumina ceramic and wear-resistant steel. The enamel layer of the invention can wet the ceramic layer, and can also improve the wettability with the wear-resistant steel substrate to form a chemical bond, and part of the enamel powder is filled into the pores of the ceramic layer, and bubbles are not easily formed between the wear-resistant steel substrate and the enamel layer, and TiO in the ceramic layer. 2-xAnd CuO as sintering aids can reduce the sintering temperature, prevent oxidation of the wear-resistant steel matrix, and improve preparation efficiency and reduce preparation costs. Chinese invention patent CN103950238A also discloses an impact-resistant ceramic composite plate, including a ceramic block, a steel plate, and a rubber plate; the area of the ceramic block and the steel plate are equal; the ceramic block and the steel plate are connected to form a ceramic-metal composite block, and a plurality of ceramic-metal composite blocks are spliced and arranged through a shock-absorbing buffer layer; the steel plate of a plurality of spliced and arranged ceramic-metal composite blocks is connected to the rubber plate. Among them, the shock-absorbing buffer layer is a rubber interlayer; the ceramic block is connected to the steel plate through epoxy resin to form a ceramic-metal composite block. This prolongs the service life of alumina ceramics, expands the scope of application, and saves a large amount of wear-resistant steel loss for mining equipment. Chinese invention patent CN103357854A also discloses a ceramic-reinforced wear-resistant steel ball, including a strengthening layer formed by brushing micron-sized ceramic particles on the inner wall of a casting mold and embedding the micron-sized ceramic particles on the surface and sub-surface of the steel ball, and the strengthening layer and the steel matrix inside the steel ball body form a layered structure from the outside to the inside. The ceramic-reinforced wear-resistant steel ball disclosed in the invention has good impact resistance, and has the advantages of high wear resistance, high hardness, and corrosion resistance. It has a larger impact energy under the same grinding conditions, thereby greatly improving the grinding efficiency, without pollution to the grinding material, ensuring the purity of the grinding material, and low comprehensive cost. Chinese invention patent CN104139172A also discloses a method for forming a mullite-based ceramic cylindrical reinforced composite wear-resistant steel plate, which includes the following process: 1. Prepare sillimanite and iron composite powder, the ratio of which is: sillimanite powder accounts for 80%wt, Fe powder accounts for 20%wt, and after mixing, press it into a round-headed cylindrical prefabricated block in a round-headed cylindrical closed extrusion mold, sinter it at 1750℃ for 2 hours at normal pressure to form mullite, and obtain a round-headed mullite-based composite material cylinder; 2. Take ordinary carbon steel As a base steel plate, a reaction pool is made of refractory bricks and sealing mud around the base steel plate, and multiple round-headed mullite-based composite material cylinders are placed on the surface of the steel plate with their round heads facing upward, leaving a certain gap between them, and the round heads of the round-headed mullite-based composite material cylinders are pressed with a steel plate with round blind holes on the surface, and molten steel is poured into the gaps of the round-headed mullite-based composite material cylinders after preheating at 300°C. The molten steel, the cylinders and the steel plate are cast and welded together to form a mullite-based ceramic cylinder-reinforced composite wear-resistant steel plate. Chinese invention patent CN102600939A also discloses a manufacturing process for a nano-zirconia ceramic-reinforced wear-resistant steel ball, in which nano-zirconia ceramics are uniformly inlaid on the surface and sub-surface of the steel ball body. Its manufacturing process includes: batching of nano-zirconia ceramics, atomization drying: screening, dry pressing densification, sintering densification, crushing and grinding powder making, steel selection, die forging into balls, high-temperature quenching, oil tempering, etc.The invention adopts nano-scale partially yttria-stabilized zirconium oxide powder to control the grain size within 100nm, and adds zirconium oxide ceramic powder to the surface of the steel ball during die forging to strengthen the surface of the steel ball, so that it has the characteristics of high strength, high toughness, good wear resistance, high temperature resistance, corrosion resistance, high rigidity, non-magnetic conductivity, and electrical insulation; its density is 6.00g / cm. 3 , Mohs hardness can be as high as 9, compressive strength 1170Mpa, thermal expansion rate close to metal thermal expansion rate, and reliably bonded with steel balls, significantly improving the strength and wear resistance of steel balls. The surface strengthening method of the invention has the advantages of low investment and quick results. Chinese invention patent CN116354740A also discloses an alumina ceramic-steel composite structure and its preparation method. The composite structure has a composite steel matrix-composite steel surface ceramic layer-alumina ceramic surface metallization layer-alumina ceramic matrix structure; the preparation method comprises: pressing raw material powders composed of steel powder, first metal powder and ceramic powder into a blank, and sintering to obtain a composite steel matrix; coating a slurry containing a second metal powder on the surface of the composite steel matrix, drying, calcining, cooling and cleaning to obtain a composite steel surface ceramic layer; using alumina ceramic as a matrix, coating or plating its surface with a third metal powder to obtain an alumina ceramic surface metallization layer; placing the surface ceramicized composite steel matrix and the surface metallized alumina ceramic in a vacuum hot pressing furnace, and connecting the composite steel surface ceramic layer and the alumina ceramic surface metallization layer by diffusion welding to obtain the alumina ceramic-steel composite structure. Chinese invention patent CN117445499A also discloses a ceramic steel and its preparation process, the preparation process includes mixing ceramic fiber, glass fiber and basalt fiber and splicing them to obtain a fiber mesh; spraying a layer of epoxy resin on a flat substrate, and after curing, obtaining an epoxy resin layer; laying a fiber mesh on the surface of the epoxy resin layer, and then spraying a layer of epoxy resin on the fiber mesh, and after curing, forming a fiber composite layer, repeating the above operation to form a multi-layer fiber composite layer; spraying a layer of epoxy resin on the surface of the multi-layer fiber composite layer, and after curing, the ceramic steel is obtained; in the preparation process of the invention, the impact resistance of the prepared ceramic steel can be improved by selecting various raw materials. In addition, by limiting different fiber diameters and lengths, the fibers are cross-filled with each other, thereby improving the impact resistance of the prepared ceramic steel, and thereby making the prepared ceramic steel have excellent anti-ballistic performance. However, the ceramic reinforced steel currently obtained generally has poor bonding effect between the ceramic and the steel matrix. Under the action of higher wear loads, the ceramic is easy to fall off, which aggravates the wear of the steel. Summary of the invention
[0005] In order to overcome the problem that the ceramic reinforcement phase of common ceramic reinforced steel has poor bonding effect with the steel matrix, which leads to easy peeling of ceramic particles due to wear load during use, the present invention proposes to synthesize high-hardness titanium carbide (TiC) ceramic phase in wear-resistant cast steel by in-situ synthesis method. In order to ensure that the TiC ceramic particles are small in size and that the ceramic reinforced steel has high wear resistance and good toughness, a composite titanium addition technology and a technology of smelting high-titanium molten steel and medium-carbon silicon-manganese-chromium alloy molten steel separately and then evenly mixing them are invented.
[0006] A ceramic particle reinforced wear-resistant cast steel and a preparation method thereof, wherein two medium frequency induction furnaces are used to smelt high titanium molten steel and medium carbon silicon-manganese-chromium alloy molten steel respectively, and the specific preparation process steps are:
[0007] ① Two medium frequency induction furnaces are used to smelt medium carbon silicon-manganese-chromium alloy steel and high titanium steel respectively; first, medium carbon silicon-manganese-chromium alloy steel is smelted in a medium frequency induction furnace, and scrap steel, ferrochrome and carburizer are mixed and heated to melt. After the molten steel is melted, ferrosilicon and ferromanganese are added in sequence. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled at 0.51-0.58%C, 1.13 ~1.28% Si, 0.55~0.74% Mn, 1.48~1.70% Cr, ≤0.040% P, ≤0.040% S, the balance is Fe and inevitable impurities; then the molten steel is heated to 1705~1718℃, and 0.05~0.08% aluminum is added to the molten steel by mass fraction in the furnace, and then the molten steel is discharged into the ladle. Before the molten steel enters the ladle, the ladle preheating temperature exceeds 650℃;
[0008] ② Use another medium frequency induction furnace to melt high titanium molten steel. When melting high titanium molten steel, the charge is 70.5-71.2% Q235 scrap steel, 4.50-4.65% carburizer, 22.0-22.8% ferrotitanium, 1.9-2.1% ferromanganese nitride and 0.12-0.15% metallic aluminum; the total mass fraction of Q235 scrap steel, carburizer, ferrotitanium, ferromanganese nitride and metallic aluminum is 100%; first, 70% Q235 scrap steel is melted into the furnace, and then the mass fraction of Q235 scrap steel is 70.5-71.2%. .5-71.2% Q235 scrap steel, 4.50-4.65% carburizer and 1.9-2.1% nitride manganese iron are mixed and heated to melt. After all the molten steel is melted, 0.5-0.6% ferrotitanium is added, and the molten steel is heated to 1612-1628℃, and 0.12-0.15% metal aluminum is added. After keeping warm for 3-5 minutes, the rest of the ferrotitanium is preheated at 850-900℃ for 100-120 minutes. After all the ferrotitanium is melted, high-titanium molten steel is obtained, and then the electric furnace is powered off. When the high-titanium molten steel in the furnace is cooled to 1407-1422°C, the high-titanium molten steel is taken out of the furnace and put into the ladle containing medium-carbon silicon-manganese-chromium alloy molten steel at 1705-1718°C in step ①; the amount of high-titanium molten steel added accounts for 46-48% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle; after all the high-titanium molten steel enters the ladle, a multi-element alloy wire is fed into the molten steel by a wire feeder, and the alloy The wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 30 to 50 mm away from the bottom of the ladle; the chemical composition and mass fraction of the alloy wire are: 22.53 to 22.96% Si, 5.64 to 5.95% Ba, 7.26 to 7.88% Mg, 6.86 to 7.39% Y, 4.70 to 5.13% Ca, <0.035% S, <0.040% P, the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire The amount of multi-element alloy wire added accounts for 0.8-0.9% of the mass fraction of molten steel entering the ladle;
[0009] ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1482-1497°C, it is poured into a resin sand or water glass sand mold. After the molten steel solidifies, the casting is taken out of the box and heat treated after grinding and sand removal;
[0010] ④ The casting obtained in step ③ is subjected to heat treatment, and the heat treatment process is: first, the casting is heated to 880-910°C in the furnace, and after being kept warm for 90-120 minutes, the casting is taken out of the furnace and oil-cooled. When the surface temperature of the casting drops to 280-350°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 260-360°C and continues to be heated to 380-400°C in the furnace. After being kept warm for 10-12 hours, the furnace is cooled to a temperature below 160°C, and the casting is taken out of the furnace and air-cooled to room temperature, so that ceramic particle reinforced wear-resistant cast steel can be obtained.
[0011] As mentioned above, the chemical composition and mass fraction of ferrotitanium are: 69.55-70.76% Ti, 1.81-2.40% Al, <0.5% Si, and the remainder is Fe and unavoidable impurities.
[0012] As mentioned above, the chemical composition and mass fraction of ferromanganese nitride are: 75.27-76.03% Mn, <0.5% C, 4.12-4.38% N, <3.5% Si, <0.3% P, <0.02% S, and the remainder is Fe and unavoidable impurities.
[0013] As mentioned above, the chemical composition and mass fraction of Q235 scrap steel are: 0.14-0.22% C, 0.17-0.32% Si, 0.30-0.65% Mn, ≤0.05% S, ≤0.045% P, and the remainder is Fe and unavoidable impurities.
[0014] In order to obtain ceramic particle reinforced wear-resistant cast steel, the present invention needs to overcome the poor bonding effect between the ceramic reinforcement phase and the steel matrix in ordinary ceramic reinforced steel, which leads to the disadvantage that the ceramic particles are easy to peel off due to the wear load during use. The present invention innovatively proposes to use an in-situ synthesis method to in-situ synthesize a high-hardness titanium carbide (TiC) ceramic phase in wear-resistant cast steel. Titanium carbide ceramic is a very important metal ceramic material with a very high hardness of 2800 to 3200 HV, which is more than twice that of high-speed steel. Titanium carbide ceramic has a high melting point, high hardness, high wear resistance, excellent chemical stability and good high-temperature stability. In order to ensure that the TiC ceramic particles are small in size and that the ceramic reinforced steel has high wear resistance and retains good toughness, the composite titanium addition technology was first invented. On this basis, the technology of smelting high-titanium molten steel and medium-carbon silicon-manganese-chromium alloy molten steel separately and then evenly mixing them was also invented. The specific preparation process steps of the present invention are implemented as follows:
[0015] The present invention adopts two medium frequency induction furnaces to smelt medium carbon silicon-manganese-chromium alloy steel and high titanium steel respectively, which can ensure that a large number of high hardness titanium carbide (TiC) ceramic hard phases with small particle size are obtained. First, the ceramic particle reinforced wear-resistant cast steel metal matrix part, that is, the medium carbon silicon-manganese-chromium alloy steel, is smelted in a medium frequency induction furnace. Scrap steel, ferrochrome and carburizer are mixed and heated to melt, and ferrosilicon and ferromanganese are added in sequence after the molten steel is melted. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled to be 0.51-0.58% C, 1.13-1.28% Si, 0.55-0.74% Mn, 1.48-1.70% Cr, ≤0.040% P, ≤0.040% S, and the balance is Fe and unavoidable impurities. The base metal of the present invention does not contain expensive metals such as molybdenum, nickel, tungsten, vanadium, niobium, etc., and has a lower production cost. The metal base part of the present invention contains 0.51-0.58% C and 1.48-1.70% Cr, which can ensure that a high-hardness martensitic base structure is obtained in the subsequent quenching process. In addition, adding 1.13-1.28% Si can ensure that the quenched martensitic base contains 3.5-4.8vol.% of residual austenite, which is beneficial to improving the toughness and plasticity of the base. Subsequently, the molten steel is heated to 1705-1718°C, and aluminum accounting for 0.05-0.08% of the mass fraction of the molten steel in the furnace is added, and then the molten steel is discharged from the furnace into a ladle. Before the molten steel enters the ladle, the preheating temperature of the ladle exceeds 650°C. The heating temperature of the molten steel is as high as 1705-1718℃, and the preheating temperature of the ladle is over 650℃, in order to ensure that the low-temperature high-titanium molten steel added subsequently can be evenly mixed with the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle, and that the gas and inclusions in the mixed molten steel can be removed from the molten steel.
[0016] At the same time, the present invention also uses another medium frequency induction furnace to melt high titanium molten steel at the same time. When melting high titanium molten steel, the furnace charge uses Q235 scrap steel with a mass fraction of 70.5-71.2% (the chemical composition and mass fraction of the Q235 scrap steel are: 0.14-0.22% C, 0.17-0.32% Si, 0.30-0.65% Mn, ≤0.05% S, ≤0.045% P, and the balance is Fe and unavoidable impurities), 4.50-4.65% carburizer, 22.0-22.8% ferrotitanium (the chemical composition and mass fraction of the ferrotitanium are: 69.55-70.76% Ti, 1.81-2.40% Al, <0.5% Si, the balance is Fe and inevitable impurities), 1.9-2.1% nitrided manganese iron (the chemical composition and mass fraction of the nitrided manganese iron are: 75.27-76.03% Mn, <0.5% C, 4.12-4.38% N, <3.5% Si, <0.3% P, <0.02% S, the balance is Fe and inevitable impurities) and 0.12-0.15% metallic aluminum; the total mass fraction of Q235 scrap steel, recarburizer, ferrotitanium, nitrided manganese iron and metallic aluminum is 100%. The furnace charge for smelting high-titanium steel of the present invention is Q235 scrap steel, recarburizer, ferrotitanium, nitrided manganese iron and a small amount of metallic aluminum. The above-mentioned furnace charge has a wide source and a low price, which can ensure that the ceramic particle reinforced wear-resistant cast steel finally obtained has a low production cost. The present invention adds a carburizer with a mass fraction of up to 4.50-4.65% and 22.0-22.8% of ferrotitanium, mainly utilizing carbon and titanium to form a high-hardness titanium carbide ceramic phase in situ, and its hardness is very high, which can reach 2800-3200 HV. However, in the ordinary smelting process of high-titanium molten steel, titanium atoms and carbon atoms will spontaneously grow under the action of high temperature and grow into coarse block TiC. Coarse block TiC exists in wear-resistant cast steel. During the wear process, under the action of wear load, due to the high brittleness of TiC, it is very easy to crack and peel off, so that the excellent wear resistance of ceramic particle reinforced wear-resistant cast steel cannot be brought into play. The present invention firstly mixes and heats 70.5-71.2% of Q235 scrap steel, 4.50-4.65% of carburizer and 1.9-2.1% of ferromanganese nitride to melt, and after all the molten steel is melted, a small amount of ferrotitanium with a mass fraction of 0.5-0.6% is added, and the molten steel is heated to 1612-1628° C. Due to the addition of 1.9-2.1% of ferromanganese nitride and 0.5-0.6% of ferrotitanium, the nitrogen element in the ferromanganese nitride and the titanium element in the ferrotitanium are easily combined to generate fine high-melting-point TiN particles, and the melting point of TiN is as high as 3000° C. Then add 0.12-0.15% by mass of metallic aluminum to play a deoxidation role. After keeping warm for 3-5 minutes, preheat the remaining ferrotitanium (most of the remaining ferrotitanium) at 850-900°C for 100-120 minutes and then add it all into the furnace. After the ferrotitanium is completely melted, high-titanium molten steel is obtained, and then the electric furnace is turned off.During the cooling process of high-titanium molten steel when the electric furnace is powered off, the high-melting-point TiN acts as the solidification and crystallization core of TiC, promoting the precipitation of TiC. When the molten steel is cooled to 1407-1422°C, the titanium element in the high-titanium molten steel is crystallized into fine high-hardness TiC ceramic particles under the action of the high-melting-point TiN solidification core.
[0017] In the present invention, when the high-titanium molten steel in the furnace is cooled to 1407-1422°C, the high-titanium molten steel is taken out of the furnace and put into the ladle filled with medium-carbon silicon-manganese-chromium alloy molten steel at 1705-1718°C in step ①; the amount of high-titanium molten steel added accounts for 46-48% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle, so that the two molten steels are mixed, which is conducive to obtaining ceramic particle reinforced wear-resistant cast steel. Since the melting point of TiC ceramic particles is as high as 3140°C, even if they are mixed with medium-carbon silicon-manganese-chromium alloy molten steel at a temperature of 1705-1718°C, the TiC ceramic particles can still exist stably. Since the density of TiC ceramic particles is small, only 4.93g / cm 3 , which is significantly smaller than the density of molten steel (7.0 g / cm 3 ), TiC ceramic particles are easy to float in molten steel and are unevenly distributed. In order to achieve uniform distribution of TiC ceramic particles in molten steel, after all the high-titanium molten steel of the present invention enters the ladle, a wire feeder is used to feed the multi-element alloy wire into the molten steel, and the multi-element alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 30 to 50 mm away from the bottom of the ladle; the chemical composition and mass fraction of the alloy wire are: 22.53 to 22.96% Si, 5.64 to 5.95% Ba, 7.26 to 7.88% Mg, 6.86 to 7.39% Y, 4.70 to 5.13% Ca, <0.035% S, <0.040% P, the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire The amount of multi-element alloy wire added accounts for 0.8-0.9% of the mass fraction of the molten steel in the ladle. The multi-element alloy wire of the present invention contains 7.26-7.88% Mg. The melting point and boiling point of magnesium element are low, with a melting point of 648.8°C and a boiling point of 1107°C. When added to high-temperature molten steel, it will be rapidly vaporized, causing the molten steel in the ladle to be violently stirred, and promoting the uniform distribution of TiC ceramic particles in the molten steel. In addition, the multi-element alloy wire also contains 5.64-5.95% Ba, 6.86-7.39% Y, and 4.70-5.13% Ca, which can promote the significant refinement of the solidification structure of the cast steel matrix, and can also reduce the number and size of inclusions in the cast steel, and significantly improve the strength and toughness of the ceramic particle reinforced wear-resistant cast steel.
[0018] After the molten steel in the ladle of the present invention is slag-stripped and left to stand, when the temperature drops to 1482-1497°C, it is poured into a resin sand or water glass sand casting mold, and after the molten steel solidifies, the casting is taken out of the box, and heat-treated after grinding and sand removal. The casting process of the present invention is simple, the production efficiency is high, and it is easy to realize industrial production. The heat treatment process of the casting is: firstly, the casting is heated to 880-910°C with the furnace, and after being kept warm for 90-120 minutes, the metal matrix can be austenitized, and after being heated to 880-910°C and kept warm for 90-120 minutes, the number, size and hardness of TiC ceramic particles will not change. After being taken out of the furnace and oil-cooled quenching, the high-temperature austenite can be converted into a high-hardness martensitic matrix. When the surface temperature of the casting drops to 280-350°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 260-360°C, which can prevent the casting after oil-cooled quenching from cracking due to excessive internal stress. Continue to heat the furnace to 380-400°C, keep warm for 10-12 hours, cool the furnace to a temperature below 160°C, and air-cool to room temperature. This can eliminate quenching internal stress, stabilize the matrix structure, and obtain ceramic particle reinforced wear-resistant cast steel with excellent toughness and wear resistance.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The present invention synthesizes high-hardness TiC ceramic particles with a volume fraction of more than 10% in situ on a high-hardness martensitic matrix. The TiC particles are small in size, less than 3 μm, and are evenly distributed on the martensitic matrix, ensuring that the ceramic particle-reinforced wear-resistant cast steel has high hardness and excellent wear resistance, and the macroscopic hardness is greater than 65HRC; a comparative friction and wear test is carried out on an MM-200 ring block wear tester, the sample size is 12mm×12mm×19mm, the grinding material is GCr15 steel, the wear load is 196N, the test machine speed is 200rmp, and the wear time is 2h. Under the same wear conditions, the wear resistance of the material of the present invention is 280%, 220% and 130% higher than that of Cr12MoV cold working die steel, M2 high-speed steel and Cr26 high-chromium cast iron, respectively.
[0021] (2) The tensile strength of the material of the present invention is greater than 1100 MPa and the impact toughness is greater than 15 J / cm 2 , has excellent strength and toughness, and is used as an anti-wear component to ensure the safe use of the anti-wear components.
[0022] (3) The material of the present invention does not contain expensive alloy elements such as nickel, molybdenum, vanadium, tungsten, and niobium, and has low production cost and simple production process. The promotion and application of the material of the present invention has good economic and social benefits. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below with reference to the examples, but the present invention is not limited to the following examples.
[0024] Example 1
[0025] A ceramic particle reinforced wear-resistant cast steel and a preparation method thereof, characterized in that two medium frequency induction furnaces are used to smelt high titanium molten steel and medium carbon silicon-manganese-chromium alloy molten steel respectively, and the specific preparation process steps are:
[0026] ① Two medium frequency induction furnaces are used to smelt medium carbon silicon-manganese-chromium alloy molten steel and high titanium molten steel respectively; first, medium carbon silicon-manganese-chromium alloy molten steel is smelted in a 1-ton medium frequency induction furnace, and scrap steel, ferrochrome and carburizer are mixed and heated to melt. After the molten steel is melted, ferrosilicon and ferromanganese are added in sequence. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled to 0.58% C, 1.13% Si, 0.74% Mn, 1.48% Cr, 0.031% P, 0.033% S, and the remainder is Fe and unavoidable impurities; then the molten steel is heated to 1718°C, and aluminum accounting for 0.08% of the mass fraction of the molten steel in the furnace is added, and then the molten steel is discharged from the furnace into a ladle. Before the molten steel enters the ladle, the preheating temperature of the ladle exceeds 650°C;
[0027] ② Another 500 kg medium frequency induction furnace was used to melt high titanium molten steel. When melting high titanium molten steel, the charge was 70.65% Q235 scrap steel (the chemical composition and mass fraction of the Q235 scrap steel were: 0.22% C, 0.17% Si, 0.65% Mn, 0.038% S, 0.041% P, the balance was Fe and unavoidable impurities), 4.50% carburizer, 22.8% ferrotitanium (the chemical composition and mass fraction of the ferrotitanium were: 70.76% Ti, 1.81% Al, 0.24% Si, the balance is Fe and inevitable impurities), 1.9% ferromanganese nitride (the chemical composition and mass fraction of the ferromanganese nitride are: 76.03% Mn, 0.19% C, 4.12% N, 2.18% Si, 0.072% P, 0.015% S, the balance is Fe and inevitable impurities) and 0.15% metallic aluminum; the total mass fraction of Q235 scrap steel, recarburizer, ferrotitanium, ferromanganese nitride and metallic aluminum is 100%; firstly, 70.65% of Q235 scrap steel, 4.50% of recarburizer and 1.9% of ferromanganese nitride are mixed and heated to melt, after all the molten steel is melted, 0.6% of ferrotitanium is added, and the molten steel is heated to 1628℃, 0.15% of metallic aluminum is added, and after keeping warm for 3 minutes, the remaining ferrotitanium is preheated at 900℃ for 1 After 00 minutes, all of them are added into the furnace. After all the titanium iron is melted, high-titanium molten steel is obtained, and then the electric furnace is powered off. When the high-titanium molten steel in the furnace is cooled to 1422°C, the high-titanium molten steel is taken out of the furnace and put into the ladle filled with 1718°C medium-carbon silicon-manganese-chromium alloy molten steel in step ①; the amount of high-titanium molten steel added accounts for 48% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle; after all the high-titanium molten steel enters the ladle, the multi-element alloy wire is fed into the molten steel with a wire feeder, and the alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 50mm away from the bottom of the ladle; the chemical composition and mass fraction of the alloy wire are: 22.96% Si, 5.64% Ba, 7.88% Mg, 6.86% Y, 5.13% Ca, 0.030% S, 0.038% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire The amount of multi-element alloy wire added accounts for 0.9% of the mass fraction of molten steel entering the ladle;
[0028] ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1497℃, it is poured into the resin sand casting mold. After the molten steel solidifies, the casting is taken out of the box and heat treated after grinding and sand removal;
[0029] ④ The heat treatment process of the casting obtained in step ③ is: first, the casting is heated to 910°C in the furnace, kept warm for 90 minutes, and then taken out of the furnace for oil cooling. When the surface temperature of the casting drops to 320-350°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 360°C and continued to be heated to 400°C. After keeping warm for 10 hours, the furnace is cooled to a temperature below 160°C, and the casting is taken out of the furnace and air-cooled to room temperature, thereby obtaining ceramic particle reinforced wear-resistant cast steel. The mechanical properties of ceramic particle reinforced wear-resistant cast steel are shown in Table 1.
[0030] Example 2
[0031] A ceramic particle reinforced wear-resistant cast steel and a preparation method thereof, characterized in that two medium frequency induction furnaces are used to smelt high titanium molten steel and medium carbon silicon-manganese-chromium alloy molten steel respectively, and the specific preparation process steps are:
[0032] ① Two medium frequency induction furnaces are used to smelt medium carbon silicon-manganese-chromium alloy molten steel and high titanium molten steel respectively; first, medium carbon silicon-manganese-chromium alloy molten steel is smelted in a 3-ton medium frequency induction furnace, and scrap steel, ferrochrome and carburizer are mixed and heated to melt. After the molten steel is melted, ferrosilicon and ferromanganese are added in sequence. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled to 0.51% C, 1.28% Si, 0.55% Mn, 1.70% Cr, 0.038% P, 0.026% S, and the remainder is Fe and unavoidable impurities; then the molten steel is heated to 1705°C, and aluminum accounting for 0.05% of the mass fraction of the molten steel in the furnace is added, and then the molten steel is discharged from the furnace into a ladle. Before the molten steel enters the ladle, the preheating temperature of the ladle exceeds 650°C;
[0033] ② Another 1.5-ton medium-frequency induction furnace was used to melt high-titanium molten steel. When melting high-titanium molten steel, the charge was 71.13% Q235 scrap steel (the chemical composition and mass fraction of the Q235 scrap steel were: 0.14% C, 0.32% Si, 0.30% Mn, 0.044% S, 0.041% P, the balance was Fe and unavoidable impurities), 4.65% carburizer, 22.0% ferrotitanium (the chemical composition and mass fraction of the ferrotitanium were: 69.55% Ti, 2.40% Al, 0.29% Si, the balance is Fe and inevitable impurities), 2.1% nitrided manganese iron (the chemical composition and mass fraction of the nitrided manganese iron are: 75.27% Mn, 0.38% C, 4.38% N, 1.86% Si, 0.12% P, 0.008% S, the balance is Fe and inevitable impurities) and 0.12% metallic aluminum; the total mass fraction of Q235 scrap steel, recarburizer, ferrotitanium, nitrided manganese iron and metallic aluminum is 100%; firstly, 71.13% of Q235 scrap steel, 4.65% of recarburizer and 2.1% of nitrided manganese iron are mixed and heated to melt, after all the molten steel is melted, 0.5% of ferrotitanium is added, and the molten steel is heated to 1612°C, 0.12% of metallic aluminum is added, and after keeping warm for 5 minutes, the remaining ferrotitanium is preheated at 850°C for 12 After 0 minutes, all of them are added into the furnace. After all the titanium iron is melted, high-titanium molten steel is obtained, and then the electric furnace is powered off. When the high-titanium molten steel in the furnace is cooled to 1407°C, the high-titanium molten steel is taken out of the furnace and placed in the ladle containing 1705°C medium-carbon silicon-manganese-chromium alloy molten steel in step ①; the amount of high-titanium molten steel added accounts for 46% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle; after all the high-titanium molten steel enters the ladle, a multi-element alloy wire is fed into the molten steel with a wire feeder, and the alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 30 mm away from the bottom of the ladle; the chemical composition and mass fraction of the alloy wire are: 22.53% Si, 5.95% Ba, 7.26% Mg, 7.39% Y, 4.70% Ca, 0.028% S, 0.037% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire The amount of multi-element alloy wire added accounts for 0.8% of the mass fraction of molten steel entering the ladle;
[0034] ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1482℃, it is poured into the water glass sand mold. After the molten steel solidifies, the casting is taken out of the box and heat treated after grinding and sand removal;
[0035] ④ The heat treatment process of the casting obtained in step ③ is: first, the casting is heated to 880°C in the furnace, kept warm for 120 minutes, and then taken out of the furnace for oil cooling. When the surface temperature of the casting drops to 280-310°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 260°C and continued to be heated to 380°C. After keeping warm for 12 hours, the furnace is cooled to a temperature below 160°C, and the casting is taken out of the furnace and air-cooled to room temperature, thereby obtaining ceramic particle reinforced wear-resistant cast steel. The mechanical properties of ceramic particle reinforced wear-resistant cast steel are shown in Table 1.
[0036] Example 3
[0037] A ceramic particle reinforced wear-resistant cast steel and a preparation method thereof, characterized in that two medium frequency induction furnaces are used to smelt high titanium molten steel and medium carbon silicon-manganese-chromium alloy molten steel respectively, and the specific preparation process steps are:
[0038] ① Two medium frequency induction furnaces are used to smelt medium carbon silicon-manganese-chromium alloy molten steel and high titanium molten steel respectively; first, medium carbon silicon-manganese-chromium alloy molten steel is smelted in a 2-ton medium frequency induction furnace, and scrap steel, ferrochrome and carburizer are mixed and heated to melt. After the molten steel is melted, ferrosilicon and ferromanganese are added in sequence. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled to 0.55% C, 1.21% Si, 0.67% Mn, 1.59% Cr, 0.032% P, 0.035% S, and the remainder is Fe and unavoidable impurities; then the molten steel is heated to 1713°C, and aluminum accounting for 0.06% of the mass fraction of the molten steel in the furnace is added, and then the molten steel is discharged from the furnace into a ladle. Before the molten steel enters the ladle, the preheating temperature of the ladle exceeds 650°C;
[0039] ② Another 1-ton medium-frequency induction furnace is used to melt high-titanium molten steel. When melting high-titanium molten steel, the charge is 70.76% Q235 scrap steel (the chemical composition and mass fraction of the Q235 scrap steel are: 0.19% C, 0.27% Si, 0.58% Mn, 0.042% S, 0.043% P, the balance is Fe and unavoidable impurities), 4.6% carburizer, 22.5% ferrotitanium (the chemical composition and mass fraction of the ferrotitanium are: 70.24% Ti, 2.18% Al, 0.26% Si, the balance is Fe and inevitable impurities), 2.0% nitrided ferromanganese (the chemical composition and mass fraction of the nitrided ferromanganese are: 75.80% Mn, 0.21% C, 4.26% N, 1.78% Si, 0.11% P, 0.011% S, the balance is Fe and inevitable impurities) and 0.14% metallic aluminum; the total mass fraction of Q235 scrap steel, recarburizer, ferrotitanium, nitrided ferromanganese and metallic aluminum is 100%; firstly, 70.76% of Q235 scrap steel, 4.6% of recarburizer and 2.0% of nitrided ferromanganese are mixed and heated to melt, after all the molten steel is melted, 0.55% of ferrotitanium is added, and the molten steel is heated to 1624°C, 0.14% of metallic aluminum is added, and after keeping warm for 4 minutes, the remaining ferrotitanium is preheated at 880°C for 11 After 0 minutes, all of them are added into the furnace. After all the titanium iron is melted, high-titanium molten steel is obtained, and then the electric furnace is powered off. When the high-titanium molten steel in the furnace is cooled to 1416°C, the high-titanium molten steel is taken out of the furnace and placed in the ladle containing 1713°C medium-carbon silicon-manganese-chromium alloy molten steel in step ①; the amount of high-titanium molten steel added accounts for 47% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle; after all the high-titanium molten steel enters the ladle, a multi-element alloy wire is fed into the molten steel with a wire feeder, and the alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 42 mm away from the bottom of the ladle; the chemical composition and mass fraction of the alloy wire are: 22.73% Si, 5.82% Ba, 7.57% Mg, 6.96% Y, 4.88% Ca, 0.023% S, 0.037% P, and the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire The amount of multi-element alloy wire added accounts for 0.85% of the mass fraction of molten steel entering the ladle;
[0040] ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1494℃, it is poured into the resin sand mold. After the molten steel solidifies, the casting is taken out of the box and heat treated after grinding and sand removal;
[0041] ④ The heat treatment process of the casting obtained in step ③ is: first, the casting is heated to 900°C in the furnace, kept warm for 100 minutes, and then taken out of the furnace for oil cooling. When the surface temperature of the casting drops to 300-325°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 310°C and continued to be heated to 390°C. After keeping warm for 11 hours, the furnace is cooled to a temperature below 160°C, and the casting is taken out of the furnace and air-cooled to room temperature, thereby obtaining ceramic particle reinforced wear-resistant cast steel. The mechanical properties of ceramic particle reinforced wear-resistant cast steel are shown in Table 1.
[0042] Table 1 Mechanical properties of ceramic particle reinforced wear-resistant cast steel
[0043]
[0044] The ceramic particle reinforced wear-resistant cast steel of the present invention does not contain expensive alloy elements such as nickel, molybdenum, vanadium, tungsten, niobium, etc., and has low production cost and simple production process. The tensile strength of the material of the present invention is greater than 1100MPa, and the impact toughness is greater than 15J / cm 2 , with excellent toughness, can be used as anti-wear parts to ensure the safe use of anti-wear parts. The ceramic particle reinforced wear-resistant cast steel of the present invention synthesizes high-hardness TiC ceramic particles with a volume fraction of more than 10% in situ on a high-hardness martensitic matrix. The TiC particles are fine in size, less than 3μm in size, and are evenly distributed on the martensitic matrix, ensuring that the ceramic particle reinforced wear-resistant cast steel has high hardness and excellent wear resistance, and the macroscopic hardness is greater than 65HRC. The material of the present invention is subjected to comparative friction and wear tests with Cr12MoV cold working die steel, M2 high-speed steel and Cr26 high-chromium casting on an MM-200 ring block wear tester. The sample size is 12mm×12mm×19mm, the grinding material is GCr15 steel, the wear load is 196N, the test machine speed is 200rmp, and the wear time is 2h. Under the same wear conditions, the wear resistance of the ceramic particle reinforced wear-resistant cast steel of the present invention is respectively improved by 280%, 220% and 130% compared with Cr12MoV cold working die steel, M2 high speed steel and Cr26 high chromium cast iron. The popularization and application of the material of the present invention has good economic and social benefits.
Claims
1. A method for preparing ceramic particle reinforced wear-resistant cast steel, It is characterized in that Two medium frequency induction furnaces are used to smelt high titanium molten steel and medium carbon silicon-manganese-chromium alloy molten steel respectively. The specific preparation process steps are: ① Two medium frequency induction furnaces are used to smelt medium carbon silicon-manganese-chromium alloy steel and high titanium steel respectively; first, medium carbon silicon-manganese-chromium alloy steel is smelted in a medium frequency induction furnace, and scrap steel, ferrochrome and carburizer are mixed and heated to melt. After the molten steel is melted, ferrosilicon and ferromanganese are added in sequence. After the ferrosilicon and ferromanganese are completely melted, the composition of the molten steel is tested, and the chemical composition and mass fraction of the molten steel in the furnace are controlled at 0.51-0.58%C, 1.13 ~1.28% Si, 0.55~0.74% Mn, 1.48~1.70% Cr, ≤0.040% P, ≤0.040% S, the balance is Fe and inevitable impurities; then the molten steel is heated to 1705~1718℃, and 0.05~0.08% aluminum is added to the molten steel by mass fraction in the furnace, and then the molten steel is discharged into the ladle. Before the molten steel enters the ladle, the ladle preheating temperature exceeds 650℃; ② Use another medium frequency induction furnace to melt high titanium molten steel. When melting high titanium molten steel, the charge is 70.5-71.2% Q235 scrap steel, 4.50-4.65% carburizer, 22.0-22.8% ferrotitanium, 1.9-2.1% nitride manganese iron and 0.12-0.15% aluminum. The total mass fraction of Q235 scrap steel, carburizer, ferrotitanium, nitride manganese iron and aluminum is 100%. First, 70.5-71.2% Q235 scrap steel, 4.50-4.65% carburizer and 1.9-2.1% nitride manganese iron are mixed and heated to melt. After the molten steel is completely melted, 0.5-0.6% ferrotitanium is added, and the molten steel is heated to 1612-1628℃, and 0.12-0.15% metal aluminum is added. After keeping warm for 3-5 minutes, the rest of the ferrotitanium is preheated at 850-900℃ for 100-120 minutes and then added into the furnace. After the ferrotitanium is completely melted, high titanium steel is obtained. water, and then the electric furnace is powered off. When the high-titanium molten steel in the furnace is cooled to 1407-1422°C, the high-titanium molten steel is taken out of the furnace and put into the ladle filled with medium-carbon silicon-manganese-chromium alloy molten steel at 1705-1718°C in step ①; the amount of high-titanium molten steel added accounts for 46-48% of the mass fraction of the medium-carbon silicon-manganese-chromium alloy molten steel in the ladle; after all the high-titanium molten steel enters the ladle, the multi-element alloy wire is fed into the molten steel by a wire feeder, and the alloy wire is inserted into the lower part of the molten steel in the ladle, and the head of the multi-element alloy wire is 30 meters away from the bottom of the ladle. ~50mm; the chemical composition and mass fraction of the alloy wire are: 22.53~22.96%Si, 5.64~5.95%Ba, 7.26~7.88%Mg, 6.86~7.39%Y, 4.70~5.13%Ca, <0.035%S, <0.040%P, the remainder is Fe and unavoidable impurities; the diameter of the multi-element alloy wire is φ3~4mm; the amount of multi-element alloy wire added accounts for 0.8~0.9% of the mass fraction of the molten steel entering the ladle; ③ After the molten steel in the ladle is slag-stripped and left to stand, when the temperature drops to 1482-1497°C, it is poured into a resin sand or water glass sand mold. After the molten steel solidifies, the casting is taken out of the box and heat treated after grinding and sand removal; ④ The heat treatment process of the casting obtained in step ③ is: first, the casting is heated to 880-910°C in the furnace, kept warm for 90-120 minutes, and then taken out of the furnace for oil cooling. When the surface temperature of the casting drops to 280-350°C, the oil-cooled casting is sent into a heating furnace with a furnace temperature of 260-360°C and continued to be heated to 380-400°C in the furnace. After keeping warm for 10-12 hours, the furnace is cooled to a temperature below 160°C, and the casting is taken out of the furnace and air-cooled to room temperature, so that ceramic particle reinforced wear-resistant cast steel can be obtained.
2. A method for preparing a ceramic particle reinforced wear-resistant cast steel according to claim 1, It is characterized in that The chemical composition and mass fraction of the titanium iron are: 69.55-70.76% Ti, 1.81-2.40% Al, <0.5% Si, and the remainder is Fe and unavoidable impurities.
3. A method for preparing a ceramic particle reinforced wear-resistant cast steel according to claim 1, It is characterized in that The chemical composition and mass fraction of the nitride manganese iron are: 75.27-76.03% Mn, <0.5% C, 4.12-4.38% N, <3.5% Si, <0.3% P, <0.02% S, and the remainder is Fe and unavoidable impurities.
4. A method for preparing a ceramic particle reinforced wear-resistant cast steel according to claim 1, It is characterized in that The chemical composition and mass fraction of the Q235 scrap steel are: 0.14-0.22% C, 0.17-0.32% Si, 0.30-0.65% Mn, ≤0.05% S, ≤0.045% P, and the remainder is Fe and unavoidable impurities.
5. A ceramic particle reinforced wear-resistant cast steel prepared according to the method according to any one of claims 1 to 4.
